The effectiveness of e-learning training in industrial safety and health:a case in FCM company - Norlinda, Mohd Rozar (2012)
In today’s economy,companies are increasingly facing challenges in a global market and rapid shifts in technology.The competition due to the economy demands people’s knowledge and skills to be constantly updated. Making a growing number of companies developed a new learning culture.In the past,companies have viewed training as a necessary expense rather than an investment.As such, emphasis was placed by cutting the expenses of training and at the same time the training is hoped to be more efficient, as it is part of investment.The knowledge and skills of the employees are now being held on equal basis with the company’s monetary asset.Learning faster than other companies represents one of the most important competitive advantages.Here the Internet technology represents an unprecedented opportunity for training departments to add value to the companies through e-learning practice.The method is viewed as cost effective and is now overwhelmingly practiced by most companies.Despite its benefits,the companies are in doubt of whether e-learning is effective enough to be a sole method of training besides it is cost effective.This is particularly true when FCM company where this study was carried out,experienced increasing number of accidents when it applies e-learning as a primary method of training.The study was conducted to 50 technical employees in the Company to determine whether participant perceive e-learning training is more effective than blended training. A survey was used during the quantitative phase with the data analyzed using an independent t test and multiple regression test.From the t test,it is found that there is a significant difference in the training effectiveness between the two methods.While,multiple regression test was used to determine whether there were correlated between the relationship of two independent variables(behavior and cost of injury)and dependent variable(training effectiveness),which yielded sufficient evidence to reject the null hypothesis that there were correlation between the variables.During the qualitative phase, interviews were used to identify the attributes that enhanced or destracted from e-learning training.Results indicated that employees demonstrated a prefer blended training over e-learning training.Even though,top managements of the company are encouraged to emphasis an e-learning due to cost-effective and at the same time translate the e-learning model into practice.